IP6 reduces colorectal cancer metastasis by mediating the interaction of gut microbiota with host genes - Lan, Tong-Tong; Song, Yang; Liu, Xiao-Han; Liu, Cui-Ping; Zhao, Hui-Chao; Han, Yi-Sa; Wang, Chu-Hui; Yang, Ning; Xu, Zhen; Tao, Meng; Li, Hui (Frontiers in Nutrition, 2022)
IP6 is a phytochemical widely found in grains and legumes that plays an anti-cancer role by regulating gut microbiota and host genes. However, the effects of IP6 on anti-tumor metastasis by regulating gut microbiota and host genes, as well as their interactions, remain unclear. In this study, 16S rRNA sequencing was used to study the effect of IP6 on gut microbiota in an orthotopic transplantation model of colorectal cancer mice. The transcriptome was used to study the changes of host genes in metastasis and the relationship with gut microbiota. The results showed that the gut microbiota composition of model mice was significantly different from that of normal mice. The beta diversity partly tended to return to the normal level after IP6 intervention. Especially, Lactobacillus_helveticus and Lactococcus_lactis were recovered after IP6-treated. Enrichment analysis showed that the enrichment score of the Cytokine-Cytokine receptor interaction signal pathway decreased after IP6 treatment compared to the model group. Further analysis of differentially expressed genes (DEGs) in this pathway showed that IP6 reduced the expression of the Tnfrsf1b gene related to the area of liver metastasis, and the Tnfrsf1b gene was negatively correlated with the relative abundance of Lactobacillus_helveticus. In conclusion, IP6 could inhibit colorectal cancer metastasis by partially restoring the changes in the gut microbiota and host transcriptome caused by metastasis and mediate the interaction between Lactobacillus_helveticus and Tnfrsf1b genes.